PARTISIPASI MASYARAKAT DALAM MUUSYAWARAH PERENCANAAN PEMBANGUNAN DI KECAMATAN CIKAKAK KABUPATEN SUKABUMI - Mulyadi (STISIP Widyapuri Mandiri, 2023)
In overcoming obstacles to community participation in development planning meetings (musrenbang), especially in the Cikakak District. This research method is descriptive with a qualitative approach. The research location is in Cikakak Sub-district and its villages spread across Cikakak Sub-district. The selection of informants was carried out by purposive sampling and snowball sampling. The data collection techniques used were unstructured interviews and frank or undercover observation. The data validity strategies used were extended observation, increased persistence, triangulation, negative case analysis and conducting member checks. Data analysis through the stages of data reduction, data presentation and verification. From the results of the research conducted, the Sukabumi District Government in analyzing community participation in the development planning process. The Cikakak Sub-district Development Planning Meeting (Musrenbang) is part of the implementation of development planning at the sub-district level. Musrenbang Kecamatan is a forum for deliberation among stakeholders. This research aims to describe community participation in the Cikakak Sub-district Musrenbang process. The aspects analyzed in community participation in the musrenbang process are forms of participation, decision-making authority and ways of providing suggestions. Data collection was conducted through observation, interview techniques and documentation studies, while the analysis technique used was descriptive qualitative Community Participation in Musrenbang.